2010
DOI: 10.4061/2010/307475
|View full text |Cite
|
Sign up to set email alerts
|

Effects of -Cystine and -Theanine Supplementation on the Common Cold: A Randomized, Double-Blind, and Placebo-Controlled Trial

Abstract: The common cold is one of the most frequent illnesses caused by viral infection. Recently, we have reported that oral administration of cystine and theanine (CT) to mice enhanced the humoral immune response associated with antibody production. Based on this mouse study, we investigated the effects of CT supplementation on the common cold in humans as a pilot study. A total of 176 healthy male volunteers were randomized to receive either placebo or CT (490 mg) tablets twice daily for 35 days. The incidence outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
(31 reference statements)
0
13
0
1
Order By: Relevance
“…In another randomized double blind and placebo controlled study conducted, 176 male individuals were given placebo or L-cysteine and L-Theanine mixture capsules (490 mg) 2 times a day for 35 days. At the end, the common cold incidence in the group given L-cysteine and L-Theanine mixture capsules was seen lower compared to the placebo group and the sickness period was the same for both groups (Kurihara et al, 2010). In a study conducted on the mice, L-cysteine and L- Theanine incited the production of antibodies specific to antigen after antigen stimulation.…”
Section: 7l-theanine and Common Coldmentioning
confidence: 95%
“…In another randomized double blind and placebo controlled study conducted, 176 male individuals were given placebo or L-cysteine and L-Theanine mixture capsules (490 mg) 2 times a day for 35 days. At the end, the common cold incidence in the group given L-cysteine and L-Theanine mixture capsules was seen lower compared to the placebo group and the sickness period was the same for both groups (Kurihara et al, 2010). In a study conducted on the mice, L-cysteine and L- Theanine incited the production of antibodies specific to antigen after antigen stimulation.…”
Section: 7l-theanine and Common Coldmentioning
confidence: 95%
“…With regard to the daily dosage and duration of cystine and theanine treatment, the daily dosage used in the present study was the same as in other studies, but the duration of treatment varied from 10 to 35 days between studies 3 , 27 30 . In the present study, these amino acids were administered for 4 days prior to surgery, over a total of 10 days; the duration of this presurgical treatment was shorter than that in other studies.…”
Section: Discussionmentioning
confidence: 82%
“…Five other studies on the effects of cystine and theanine administration in humans have been reported 3 , 27 30 . The first was a study of malnourished elderly patients in whom significantly increased antibody levels after influenza vaccinations were observed with administration of cystine and theanine 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The body's defence against foreign molecules relies on the homeostatic regulation of innate and adaptive immune systems [71]. Conventional methods of treatment for common illnesses usually involve a regimen of antibiotics, antivirals, immunosuppressant's and dietary intervention that may support or enhance immune function [72]. A number of recent studies have suggested that L-THE administration can improve the body's immune system.…”
Section: Immune Systemmentioning
confidence: 99%